1977
DOI: 10.1007/bf01869514
|View full text |Cite
|
Sign up to set email alerts
|

Changes in absorption, fluorescence, dichroism, and birefringence in stained giant axons: Optical measurement of membrane potential

Abstract: The absorption, fluorescence, dichroism, and birefringence of stained squid axons were measured during action potentials and voltage clamp steps in an effort to find large optical signals that could be used to monitor membrane potential. Changes in all four optical properties were found that were linearly related to membrane potential and, with several new dyes, the signal-to-noise ratios were larger than any obtained previously. The problem of photodynamic damage was greatly diminished; with a merocyaninerhod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
202
2

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(217 citation statements)
references
References 35 publications
13
202
2
Order By: Relevance
“…Previous work has shown that certain voltage-sensitive dyes have little or no pharmacological effect when applied from the outside or inside to some invertebrate neurons within a limited concentration range (Ross et al, 1977;Gupta et al, 1981;Antic and Zecevic, 1995). With mitral cells, we found that the resting membrane potential and action potentials recorded electrically from the soma were not affected during the staining period (Fig.…”
Section: Methodsmentioning
confidence: 54%
“…Previous work has shown that certain voltage-sensitive dyes have little or no pharmacological effect when applied from the outside or inside to some invertebrate neurons within a limited concentration range (Ross et al, 1977;Gupta et al, 1981;Antic and Zecevic, 1995). With mitral cells, we found that the resting membrane potential and action potentials recorded electrically from the soma were not affected during the staining period (Fig.…”
Section: Methodsmentioning
confidence: 54%
“…It is evident that the delays between the action signals at a higher sweep speed corresponds to the progressive retardation due to conduction velocity of the electrical excitation. In experiments using the bull-frog (liana catesbeiana) atrium stained with a merocyanine-rhodanine dye (dye XVII in Ross et al, 1977), we found that the conduction velocity assessed using optical recording was in fairly good agreement with that obtained using microelectrodes; the velocity was 0.20 m/sec using the optical recording and 0.24 m/ sec using the microelectrode method (SAWANOBORI et al, 1981).…”
Section: Discussionmentioning
confidence: 73%
“…This pioneered the use of voltage-sensitive dyes to measure changes in membrane potential and was first used to record changes in intracellular membrane potential from single neurons of the leech segmental ganglion [48]. These studies paved the way for the search and development of better voltage-sensitive dyes with increased signal to noise [12,18,23,34,45], with the promise of an optical solution to measuring changes in membrane potential in neurons in both time and space. This goal was realized with the introduction of photodiode arrays allowing the activity of multiple neurons to be monitored simultaneously [17,20,49].…”
Section: Development Of Voltage-sensitive Dyesmentioning
confidence: 99%